Community college as a lifesong or swansong for the underrepresented population: a holistic critical theory perspective - Wolfe, David Leland, author; Davies, Timothy Gray, 1942-, advisor; Banning, James H., advisor; Hall, Bruce, committee member; Awasu, Wilson, committee member (Colorado State University. Libraries, 2011)
Holistic critical theory seeks to explicate class, ethnicity, and gender issues. This perspective will be used to explore justice and inequities that face the underrepresented population at All Peoples Community College, a fictitious college. The underrepresented population in this community college context included: the poor; first-generation; those who experienced the foster-care system; Asian-, African-, and Native American; and Hispanic students; and finally welfare-mother students with children and is referred to as the Other. Holistic critical theory not only includes the rational values of Critical Theory, but also a the values of spirituality, and interculturalism. Spirituality has a significant influence in the discourse in adult learning theories and higher education and is define secularly (non-religiously) with three components: To know oneself; To develop an ethic of care; and to know the Other. Interculturalism is defined by Deardorff's (2005) work using intercultural experts to define intercultural competence. She found 44 key elements concentrating primarily on communication and behaviors of a person functioning in an intercultural context. Nussbaum (1997) used the term interculturalism to extend the principals of diversity and multiculturalism. She defined interculturalism as a comparative searching that recognizes the common human needs across cultures and of dissonance and critical dialogue within cultures. I extend this a bit to allow the possibility to be transformed by culturally different Others. Interculturalism is transformative and is accomplished by having profound conversations, which imply deep listening, seeking profound understanding, and encouraging internal and potentially external changes based upon new knowledge.
Keywords: critical theory; diversity; first-generation; interculturalism; spirituality; underrepresented